PERANCANGAN APLIKASI E-RECRUITMENT BERBASIS WEB DENGAN NOTIFIKASI SMS GATEWAY DI PT. AGUNG KARUNIA UTAMA - Waliadi Gunawan; Masum Masum; Aang Rizkiana (Program Studi Sistem Informasi, Universitas Banten Jaya, 2019)
In this advanced technology, the need of information is needed in supporting the accurate, on time, and relevant information, The information got from the process of a system of information. Thereforem a company needs a computerized system of information. It began with the efforts of PT. Telekomunikasi Indonesia to have a partnership in the field of telecommunication. Thus, PT. Agung Karunia Utama was chosen as one of the contracted partners in the form of letter of partnership.In recruiting that is in collecting application files sent by the applicants that are selected in the form of documents that will take the time to select the files one by one continually, and it will make the obstacles in selecting the data of applicants. The candidates of applicant send the files of application in the form of hard copy used in administration selecting, then from the side of HRD should input the data of the candidates on by one into the database, so it need a longer time to the process of administration selection. With the advanced IT, e-recruitment by using company website as the effective method. Since it gives the opportunities to know more about the company only but it also can give the detailed descriptionabout the offered job. The using of e-recruitment helps the company to run the process of recruitment that is fast, effective and resulting consistently.